When the Politics of Food and Politics of Immigration Collide— Who Wins? - Ginley, Barbara (Maine Policy Review, 2011)
This commentary discusses how migrant workers play a key role in Maine and national agriculture, a key fact that is sometimes lost in the political rhetoric about “illegal immigrants.”